Placental microRNA expression associates with birthweight through control of adipokines: results from two independent cohorts. Issue 7 (3rd July 2021) - Kennedy, Elizabeth M.; Hermetz, Karen; Burt, Amber; Everson, Todd M.; Deyssenroth, Maya; Hao, Ke; Chen, Jia; Karagas, Margaret R; Pei, Dong; Koestler, Devin C; Marsit, Carmen J
ABSTRACT: MicroRNAs are non-coding RNAs that regulate gene expression post-transcriptionally. In the placenta, the master regulator of foetal growth and development, microRNAs shape the basic processes of trophoblast biology and specific microRNA have been associated with foetal growth. To comprehensively assess the role of microRNAs in placental function and foetal development, we have performed small RNA sequencing to profile placental microRNAs from two independent mother-infant cohorts: the Rhode Island Child Health Study (n = 225) and the New Hampshire Birth Cohort Study (n = 317). We modelled microRNA counts on infant birthweight percentile (BWP) in each cohort, while accounting for race, sex, parity, and technical factors, using negative binomial generalized linear models. We identified microRNAs that were differentially expressed (DEmiRs) with BWP at false discovery rate (FDR) less than 0.05 in both cohorts. hsa-miR-532-5p (miR-532) was positively associated with BWP in both cohorts. By integrating parallel whole transcriptome and small RNA sequencing in the RICHS cohort, we identified putative targets of miR-532. These targets are enriched for pathways involved in adipogenesis, adipocytokine signalling, energy metabolism, and hypoxia response, and included Leptin, which we further demonstrated to have a decreasing expression with increasing BWP, particularly in male infants. Overall, we have shown a robust and reproducible association of miR-532 with BWP, which could influence BWP through regulation of adipocytokines Leptin and Adiponectin.